Welfare resilience in the first month of COVID-19 pandemic in Italy - Francesco Figari; Carlo Fiorio (University of Essex, Centre for Microsimulation and Policy Analysis (CeMPA), 2020)
This paper analyses the extent to which the Italian welfare system provides a monetary compensation for those who lost their earnings due to the lockdown imposed by the government in order to contain the COVID-19 pandemic in March 2020. In order to assess the potential impact of the first-order effects of the businesses temporarily shut down and the policy measures introduced by the government on household income, counterfactual scenarios are simulated by using EUROMOD, the EU-wide microsimulation model, integrated with information on the workers more likely to be affected by the lockdown. This paper provides timely evidence on the differing degrees of relative and absolute resilience of the household incomes of the individuals affected by the lockdown. These arise from the variations in the protection offered by the tax-benefit system and from the personal and household circumstances of those most recently at risk of earning losses.
Keywords: 330; Health; Labour Market; Households; Income Dynamics; Microsimulation; Covid-19; Taxation; Welfare Benefits; Economics; Public Policy; Wages And Earnings